Psychosocial Safety Climate And Burnout Among Malaysian Research University Academicians: The Mediating Roles Of Work Engagement And Job Demands - Teoh, Kok Ban (2020)
This study builds a research framework to govern the investigation of psychosocial safety climate, challenge demands, hindrance demands and work engagement as the predictors of burnout level with work engagement, challenge demands and hindrance demands as the mediating variables.